Effective and Efficient: Large-scale Dynamic City Express - Zhang, Siyuan; Qin, Lu; Zheng, Yu; Cheng, Hong (IEEE Transaction on Knowledge and Data Engineering, 2016)
Due to the large number of requirements for city express services in recent years, the current city express system is found to be unsatisfactory for both the service providers and customers. In this paper, we are the first to systematically study the large-scale dynamic city express problem. We aim to increase both the effectiveness and the efficiency of the scheduling algorithm. The challenges of the problem stem from the highly dynamic environment, the NP-completeness with respect to the number of requests, and real-time demands for the scheduling result. We introduce a basic algorithm to assign a request to a courier on a first-come, first-served basis. To improve the effectiveness of the basic algorithm, we adopt a batch assignment strategy that computes the pickup-delivery routes for a group of requests received in a short period rather than dealing with each request individually. To improve the efficiency of the algorithm, we further design a two-level priority queue structure to reduce redundant shortest distance calculation and repeated candidate generation. We develop a simulation system and conduct extensive performance studies on the real road network of Beijing city. The experimental results demonstrate the high effectiveness and efficiency of our algorithms. Remarkably, our system can achieve much better service quality and largely reduce the operation cost of a city express company simultaneously.